Effect of Weaning Management on Performance of Growing Finishing Crossbred (Tamworth x Desi) Pigs under Farm Condition of Assam (Indian Journal of Animal Production and Management, 2016)
The present study was carried out on 24 growing finishing crossbred (Tamworth x Desi) pigs maintained at  All India Coordinated Research Project on Pig (under Mega Seed Project), College of Veterinary Science,  Assam Agricultural University, Khanapara, Guwahati, Assam. Six castrated grower pigs of average body  weight (25.88 kg) at the end of rearing period (13 weeks of age) were selected from the litters of 5 sows (at  least one grower pig per litter) which were weaned at 28 days of age. Similarly, 18 other castrated grower  pigs (six per weaning group) were selected from the litters of 15 sows (5 sows in each weaning group)  which were weaned at 35, 42 and 56 days of age. The selected pigs were reared individually and reared  under farm condition till the end of slaughter age (34 weeks of age). All the experimental animals were fed  to the appetite on concentrate rations prepared as per the standards given by NRC (1998). Pigs weaned  early (28 or 35 days), having significantly (P
Keywords: Average daily gain; Body weight; Crossbred pig; Feed conversion efficiency; Weaning